(untitled) (Journal of Naval Architecture and Marine Engineering, 2020)
E-learning has become a widespread form of education as it allows the users a relatively easy access to needed information. E-learning has also been present in maritime affairs, although not so ubiquitous as in other economy sectors. Sea-borne shipping is one of the most stringently controlled industries, with a number of complex regulations and standards. This paper analyses learning methodologies and discusses the economic justification of implementing e-learning systems at global level, with an emphasis on the growing e-learning industry, corporate segment of e-learning, massive open online course market, and the importance of the micro-learning concept. In addition, this study analyses the present systems of seafarers’ education and the potentials, strengths and shortcomings of the conventional learning, e-learning and m-learning. Moreover, the recent application of e-learning in maritime affairs and the need of further research of the e-learning impacts in maritime affairs are examined. Finally, the presented information and discussion result in the logic matrix analysis and the SWOT analysis of e-learning, aiming to define the strengths, weaknesses, logic of action, goals and potentials of the implementation of e-learning in maritime affairs. Keywords: E-learning, education of seafarers, STCW Convention, IMO.